Teaching Evidence-Based Medicine in The Former Soviet Union: Lessons Learned - Telen, Marilyn J. (American Clinical and Climatological Association, 2014)
Between 2009 and 2012, I taught principles of evidence-based medicine and clinical research in Russia, Tatarstan, Moldova, and Kazakhstan. The Soviet Union left a medical legacy characterized by balkanization of top tier medicine in highly specialized centers, so there was little capability for multidiscipinary care. In addition, the authoritarian government led to a persistently top-down tradition of medical education and practice, which one of my Russian colleagues aptly named “eminence-based medicine.” After the fall of the Soviet Union, funding for science and medical research was drastically cut, leading to a struggle for resources and politicization of resource decisions. At present, prejudices and beliefs about disease and treatment persist untested, limited English language competency impedes acquisition of new knowledge, and restriction of resources cripples innovation. Yet none of these conditions are unknown to us in the United States. Physicians may resist evidence that challenges long-held beliefs, and patients want us to make decisions based on their individual case, not evidence arising from studying other people. As physicians, we need to understand how to communicate with and frame our arguments so that they can be understood and received favorably. Can we draw lessons from trying to teach evidence-based medicine in the former Soviet Union?